Can Self-healing Mechanism Helps Concrete Structures Sustainable?. (2017) - Sangadji, Senot
Abstract: Concrete is quasi-brittle material susceptible to cracking under tensile or shear stress. In case of continuous network of crack is formed, concrete structure becomes permeable and embedded rebar may be exposed to ambient air, hence escalating the risk of material degradation. On the other side, concrete infrastructures industry is facing pressing sustainability issues. Concrete production consumes high amount of energy and produces large amount of CO2 emission. The scale of the problem is even greater in the event of many concrete structure premature failure which consumes more raw material for rebuilding. Designing new infrastructures for longer service life by improving concrete (materials and structure) durability is one solution to overcome the dilemma. One promising concept is by incorporating self-healing mechanism found in nature into cement-based materials / concrete structural element. This paper presents inherent autogeneous healing which occur due to its heterogeneous nature of concrete. This contribution also demonstrates some laboratory proven bio-inspired techniques that makes concrete materials and/or structural element self-healing autonomously. It involved diverse methods across several categories. The methods designed have demonstrated to have a good prospect in making concrete structural element self-healing. Finally the paper concludes with the claim that If unavoidable cracks due to inherent brittleness in concrete could be self- sealed/healed/repaired, concrete structure will certainly serve longer service life, making it more durable, therefore sustainable.